Nodular posterior scleritis with associated choroiditis masquerading as a choroidal tumour- A Case Report - Muhammad Amer Awan; Mohsin, Fatima; Abdullah Ahmed; Muhammad Suhail Sarwar; Tahir Hashmi (Journal of the Pakistan Medical Association, 2023)
We report a case of nodular posterior scleritis in a 25-year-old male who presented with a 14-day history of unilateral decline in vision, pain, and redness in his right eye. Slit lamp examination of the right eye revealed dilated episcleral vessels present nasally as well as a choroidal mass at the nasal periphery of the fundus, associated with choroidal oedema. Systemic evaluation and imaging of the choroidal mass were performed to rule out choroidal tuberculoma and choroidal metastasis. Ultrasound B-scan of the right eye showed marked thickening of the nasal sclera resulting in sympathetic choroidal oedema without the characteristic T-sign. Nodular posterior scleritis with associated choroiditis, was diagnosed without any underlying systemic illness. The patient was immediately started on systemic steroids and later on subcutaneous Methotrexate as advised by the rheumatologist, to which he responded well and his vision significantly improved from 6/60 to 6/9, gradually during his treatment course.